STRENGTHENING CHARACTER IN THE PANCASILA LEARNER PROFILE THROUGH HABITUATION METHODS IN ELEMENTARY SCHOOL - Nisa, Haniffatun; Utami, Ratnasari Diah (Universitas Pendidikan Indonesia, 2024)
Habituation activities at school can shape the character of devotion to God Almighty and noble character. The problems of bad student attitudes, such as the tendency of students to cheat, disrespect teachers, and et cetra are still often in schools today. The study purpose to describe the strengthening of the character of faith and devotion to God Almighty and noble character through the habituation method in SDIT Muhammadiyah Al-Kautsar Kartasura students. This research uses qualitative methodology. The data sources in this study were principals, teachers, and students at SDIT Muhammadiyah Al-Kautsar Kartasura. Data collection techniques used in this study include observation, interviews, and documentation. The data validity test uses source and technique triangulation and crosscheck. The data obtained were then analyzed through data reduction, data display, and conclusion drawing. The results showed that the program carried out by the school to strengthen the character of faith, fear of God Almighty and noble character by implementing a habituation program in each key element. Religious morals are realized in the habituation of morning prayer, congregational prayer, morning and evening dhikr. Personal morals are realized through the 5S culture, rules, and role models. Manners to humans are realized in the habituation of greeting, and social activities. Manners towards nature are carried out by practicing clean Fridays, caring for plants, and throwing garbage in its place. For the morals of the state, it is realized in the habituation of ceremonies every Monday and holidays and the existence of traditional dance extracurriculars